Spying on the South : an Odyssey Across the American Divide - Horwitz, Tony 1958- (New York : Penguin Press, 2019)
"The author retraces Frederick Law Olmsted's journey across the American South in the 1850s, on the eve of the Civil War. Olmsted roamed eleven states and six thousand miles, and the New York Times published his dispatches about slavery and its defenders. More than 150 years later, Tony Horwitz followed Olmsted's route, and whenever possible his mode of transport--rail, riverboats, in the saddle--through Appalachia, down the Ohio and Mississippi, through Kentucky, Tennessee, Louisiana, and across Texas to the Rio Grande, discovering and reporting on vestiges of what Olmsted called the Cotton Kingdom"--
Includes bibliographical references and index.
Keywords: Olmsted, Frederick Law, -- 1822-1903 -- Travel -- Southern States; Horwitz, Tony, -- 1958- -- Travel -- Southern States; Southern States -- Description and travel